2012
DOI: 10.1055/s-0039-1698949
|View full text |Cite
|
Sign up to set email alerts
|

Study of thyroid hormones free triiodothyronine (FT3), free thyroxine (FT4) and thyroid stimulating hormone (TSH) in subjects with dental fluorosis

Abstract: Objective:Apart from its well-known deleterious dental and skeletal effects, fluoride excess can have toxic effects on many other tissues. Fluoride, when in excess, is known to interfere with thyroid gland function. Fluoride-induced thyroid disturbances similar to those observed in iodine deficiency state in spite of adequate iodine intake have been documented. Similar thyroid disturbances in individuals with dental fluorosis have not been well studied in populations with endemic fluorosis. This work was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…[ 11 17 22 ] All in all, the balance between the achievement of maximum protection against dental caries and the risk of development of fluorosis should be taken into consideration. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 17 22 ] All in all, the balance between the achievement of maximum protection against dental caries and the risk of development of fluorosis should be taken into consideration. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…For example, Michael et al (1996) 5 found no difference in the levels of thyroid-stimulating hormone (TSH) between those with low and high fluoride exposure (fluoride exposure was not clearly defined), whereas Lin et al (1991) 8 found that individuals residing in high fluoride areas (defined as areas with an average fluoride concentration of 0.88 parts per million (ppm) in drinking water) had significantly higher TSH levels than those residing in low fluoride areas (average fluoride concentration of 0.34 ppm in drinking water) (p<0.01). Conversely, a study by Hosur et al (2012) 9 did not detect altered levels of thyroid hormones (free T3, free T4 and TSH) in 65 individuals living in India with dental fluorosis (used as a proxy for high fluoride exposure), with the exception of one individual whose serum levels of TSH were elevated. The results of these small-scale human studies should be interpreted with caution in light of limited details regarding the study sample, unclear descriptions of fluoride exposure classification and lack of adjustment for other important covariates (eg, iodine status).…”
Section: Introductionmentioning
confidence: 88%
“…Among subjects with dental fluorosis, they didn't observe any significant alteration in the thyroid hormone levels. 13 For the assessment of the severity of dental fluorosis, along with thyroid function and bone metabolic indicators among school children, Khandare et al conducted a case-control study. They carried out the investigation in the area where drinking water was contaminated, and heat stressed.…”
Section: Discussionmentioning
confidence: 99%